Pewarisan Anak Yang Lahir dari Perkawinan Campuran Dalam Perspektif Hukum Adat Bali - Krisna, Anak Agung Gede; Mas Rwa Jayantiari, I Gusti Agung (Acta Comitas, 2023)
The objective of this journal is to comprehend the citizenship status and inheritance of children from mixed marriages from the perspective of Balinese customary inheritance law. this paper in normative research legal is use with a legislative aproach as well as legal. The results on this research how the citizenship status of a child resulting from a mixed marriage will only be considered an Indonesian citizen if the citizenship he obtained from his parents' marriage resulted in him having two citizenships. It is clear that a child, once eighteen years of age or married, must choose citizenship. The inheritance of children's rights in mixed marriages from the perspective of Balinese customary law is determined by the form of marriage carried out by the parents, which adheres to Indonesian marriage and Balinese customary inheritance law. If the mother is a Balinese woman and the father is a foreigner with a normal marriage, it is that the law that applies to the marriage is the marriage law that originates from the father. If the mother is a Balinese woman and the father is a foreigner who has a nyeburin form of marriage, then the law that is applied from the marriage is customary law. Bali, and children's inheritance rights are determined by the mother's law, in this connection is Balinese customary law.